Pengaruh Kondisi Jalan Terhadap Minat Wisatawan Untuk Berlibur di Pantai Balekambang Kabupaten Malang - Wahyu Sugeng Suratman; Jeni Susyanti (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Roads are the main component supporting economic mobility in an area, the condition of the road both will be able to lift the wheels of the regional economy. The south malang area is in the coastal tourist area, there are many beach tourist destination that you can go to holiday. Road conditions are of the main components supporting development area tourism in the south malang area. Good road conditions can increase interest tourist to visit and vice versa, so it is important to maintain the condition of the roads remain in very good condition.